Environmental Information Systems in Sub-Saharan Africa: Investing in the Future - Pavy, Jean-Michel (World Bank, Washington, DC, 2012)
The World Bank, together with other donors, has launched a program for promoting information systems in Sub-Saharan Africa. Because of the importance of geo-referenced information systems in resource decision-making, a systematic review of the Bank portfolio in Sub-Saharan Africa has been carried out from Fiscal Year (FY) 1988 to FY 1993. This review assesses if the Bank commitment to developing geo-referenced information systems has been translated into its operation; draws and disseminates lessons; and formulates recommendations. The main findings are as follows: 1) the World Bank commitment to developing geo-referenced information systems is not yet reflected in its operations. 2) Investment in geo-referenced information systems has been concentrated in only a few countries and projects. 3) There are no clear trends in investment over time; but differences appear among Country Departments, some of them focusing more on the development of geo-referenced information systems than others. 4) Land titling, and more recently, environmental planning seem to stimulate investment in geo-referenced systems. The report ends with recommendations to promote and develop information systems in Africa and to promote and develop information systems within the Bank and donor agencies.